ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN E-WALLET SELAMA MASA PANDEMI COVID-19 DI INDONESIA - Gilda Azalia Nur Ramadhani, (2022)
This study analyzes the interest in intention to use e-wallet in Indonesia during the Covid-19 pandemic. This study aims to understand the factors that influence the interest in using e-wallet in Indonesia. The factors analyzed are perceived usefulness, perceived ease of use, and compatibility. 206 respondents were used as samples with the criteria of students studying in Indonesia and e-wallet users. Data was collected through questionnaires distributed via Google forms in the student community and social media (Instagram and Twitter). Data processing using Partial Least Square (PLS). The results of the analysis show that perceived usefulness, perceived ease of use, and compatibility have influence on intention to use.